What is to be done about crime and punishment? towards a 'public criminology' - Matthews, Roger 1948-2020 (Palgrave Macmillan, 2016)
"This book responds to the claim that criminology is becoming socially and politically irrelevant despite its exponential expansion as an academic subdiscipline. It does so by addressing the question "what is to be done" in relation to a number of major issues associated with crime and punishment. The original contributions to this volume are provided by leading international experts in a wide range of issues. They address imprisonment, drugs, gangs, cybercrime, prostitution, domestic violence, crime control, as well as white collar and corporate crime"--
Keywords: Criminology; Crime; Family violence; Gangs; Criminal justice, Administration of; Imprisonment; Drug control; White collar crimes; Computer crimes; Prostitution; Kriminologie; Aufsatzsammlung